1991
DOI: 10.1002/mrd.1080300315
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative changes in protein sythesis of bovine follicular cells during the preovulatory period

Abstract: To understand the mechanisms governing oocyte maturation better, the effects of the gonadotropin surge were studied on follicular cells of bovine preovulatory follicles. For this purpose, qualitative and quantitative changes in protein synthesis by both granulosa cells and cumulus cells were compared relative to the luteinizing hormone (LH) surge and the resumption of meiosis in the oocyte. Follicular cells were collected at different times before and up to 25 hr after the LH surge. For each individual preovul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…GSTAs were found to be major cytosolic proteins in the bovine adrenal cortex (28). Similarly, we have observed a major group of 28 kDa proteins as demonstrated herein and a previous study (4). In the bovine adrenal gland study (28), two GSTAs were observed: a major protein band at 25.9 kDa estimated to contribute to 1.3% of the cytosolic protein content, and a minor protein band at 26.5 kDa.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…GSTAs were found to be major cytosolic proteins in the bovine adrenal cortex (28). Similarly, we have observed a major group of 28 kDa proteins as demonstrated herein and a previous study (4). In the bovine adrenal gland study (28), two GSTAs were observed: a major protein band at 25.9 kDa estimated to contribute to 1.3% of the cytosolic protein content, and a minor protein band at 26.5 kDa.…”
Section: Discussionsupporting
confidence: 61%
“…A group of 28 kDa proteins was shown to constitute one of the conspicuous groups of proteins in bovine granulosa cells (4). In this latter study, it was shown that the expression of the 28 kDa protein group was reduced when granulosa cells from bovine preovulatory follicles were treated with LH.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The importance of the cumulus cells for the final maturation and developmental competence of immature oocytes has been well established (reviews [1][2][3]). The relationship that exists in vivo between the mural granulosa cells and the cumulus-oocyte complexes has been studied throughout the preovulatory period in cattle [4]. Three major protein groups of approximately 76 kDa, 56-58 kDa, and 28-30 kDa were identified on SDS-PAGE analysis following de novo 35 S-metabolic labeling of granulosa cells collected from preovulatory follicles.…”
Section: Introductionmentioning
confidence: 99%